UPAYA PENINGKATAN KESADARAN MASYARAKAT DALAM PEMANFAATAN LIMBAH MINYAK JELANTAH DI DESA LENGGAHJAYA - Ardiyudha Wiratama, Rayhan; Salman Wijiana, Farid; Aprenia, Lysa; Syarifah, Nurdina; Budiman, Rido; Rikmasari, Rima (Universitas Islam 45 Bekasi, 2023)
Health is something that is the main focus for every country. When a country has a healthy society, its people will also become more productive. It is important for the community to always implement healthy living behavior, of course, before implementing healthy living behavior, first increase public awareness of the importance of implementing healthy living behavior in everyday life. Apart from that, what is still a problem is that many people do not realize that creating a healthy society requires efforts to create a healthy environment as well. Such as protecting the environment from waste that can damage the environment if it is continuously thrown away carelessly. One of them is used cooking oil waste which is still the center of attention, especially in Indonesia. The methods used in this service program are observation and interviews, outreach, environmental advocacy. The activity that will be carried out is an effort to increase public awareness regarding the use of used cooking oil waste in Lenggahjaya Village. The results of this service program provide benefits in the form of increasing public awareness of the dangers of used cooking oil waste for health and the surrounding environment and the public knowing that used cooking oil waste can be reprocessed into production materials, as has been practiced, namely processing it into aromatherapy candles.